Antigenic and Genetic Analysis of Foot and Mouth Disease Virus Isolates from 2005 to 2009 in Saudi Arabia for Selection of Candidate vaccine strains (Journal of Advanced Veterinary Research, 2012)
Foot and mouth disease (FMD) is considered one of the enzootic animal diseases in Saudi Arabia. During the period 2005-2009, large numbers of FMD type O outbreaks were reported and related to FMDV ME-SA Pan Asia II topotype. FMD type A virus was only detected in December 2005. Its phylogenetic analysis confirmed that this type A virus was a member of the ASIA topotype. Our results of molecular-biological studies revealed that FMDV type O Manisa that present in the current vaccine formula appears to have only a moderate match against some isolates of the currently circulating FMDV type O PanAsia strain while FMD type A virus was most closely related to the Iranian A/Iran /2005. So, the authors recommend using a tetravalent vaccine containing type O FMDV PanAsia topotype, type A Iran 2005, Asia1 and Sat2 for FMD prevention in the large Saudi Arabian dairy farms. In addition to, bivalent vaccine containing type O FMDV PanAsia topotype and type A Iran 2005 for the routine vaccination campaigns all over the country.